The Effect of Well Completion Fluid Loss on Productivity Evaluation in Tight Sand Gas Reservoir: A Case Study from East China Sea Gas Well - Kechao Gao; Suogui Shang; Xuan Wu; Liang Tao; Yutang Jin (International Journal of Petroleum Technology, 2020)
Fluid loss is inevitable in the well drilling and completion, which may cause series of formation damage such as clay swelling, solid plugging and water blocking. In tight sand gas reservoir, water blocking has become the major damage factor for economical developing. In deliverability test, water blocking will bring an inaccurate productivity test result to affect the following development strategy. With the development of East China Sea gas field, well drilling is focusing on the deeper tight sand formation. The tiny pore throat and high capillary pressure can bring out serious water blocking damage during well drilling and completion. The damaged zone can mislead the resource assessment and productivity evaluation. In this paper, an exploration well X in East China Sea gas field is selected as the research target to investigate the water blocking mechanism and physical process during well drilling and completion process. This study compares the productivity performance of X well with fluid loss and no fluid loss models through numerical modeling approach based on the actual data. Sensitive studies are also performed in the simulation. Results show that the excessive fluid invasion pressure and lower matrix permeability will result in serious water blocking damage to mislead the resource assessment and productivity evaluation even in underbalanced well drilling. Interestingly, extending shut-in time can make the gas production rate quickly reach the peak value in the early production stage, while it can decrease the cumulative gas production in whole production process. This study can provide an avenue to initiate quantitative analysis on resource assessment, and gas productivity evaluation strategy after water invasion during the well drilling and completion in tight sand gas reservoir of East China Sea.